Women on the edge : four plays - Euripides (New classical canon., 1999)
Women on the Edge, a collection of Alcestis, Medea, Helen, and Iphegenia at Aulis, provides a broad sample of Euripides' plays focusing on women, and spans the chronology of his surviving works, from the earliest, to his last, incomplete, and posthumously produced masterpiece. Each play shows women in various roles--slave, unmarried girl, devoted wife, alienated wife, mother, daughter--providing a range of evidence about the kinds of meaning and effects the category woman conveyed in ancient Athens. The female protagonists in these plays test the boundaries--literal.